2019
DOI: 10.1007/978-3-030-03676-8_4
|View full text |Cite
|
Sign up to set email alerts
|

Negotiated Materialization: Design Approaches Integrating Wood Heterogeneity Through Advanced Robotic Fabrication

Abstract: Whilst robots are predictable, repetitive, predefined and constant, natural materials present unpredictable complexity. Over the past few centuries, materials have been standardized to fit industrial processes, in an attempt to defy this unpredictability. Thanks to new advances in sensing technologies and computational design, today we have the opportunity to reintegrate the intrinsic properties of natural materials in their full complexity. What is the potential of a synthesis between the particularity of eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…En un modelo CAD tridimensional, la representación idealizada de un miembro lineal de madera, es suficiente para realizar simulaciones estructurales (Kohlhammer et al, 2017) pero para muchos procesos sustractivos de piezas de geometría compleja, aparecen problemas adicionales cuando se trata del montaje de materiales que tienen tolerancias muy altas (Stumm et al, 2017). Estas tolerancias o errores, independiente de su origen, se acumulan durante las diversas fases del proyecto, desde la fabricación hasta el montaje de componentes (Brugnaro et al, 2019). Muchos de estos errores se han resuelto en el estado del arte mediante la implementación de mecanismos de retroalimentación basados en sensores que permiten absorber las incongruencias entre la realidad física y los modelos digitales.…”
Section: Discussionunclassified
“…En un modelo CAD tridimensional, la representación idealizada de un miembro lineal de madera, es suficiente para realizar simulaciones estructurales (Kohlhammer et al, 2017) pero para muchos procesos sustractivos de piezas de geometría compleja, aparecen problemas adicionales cuando se trata del montaje de materiales que tienen tolerancias muy altas (Stumm et al, 2017). Estas tolerancias o errores, independiente de su origen, se acumulan durante las diversas fases del proyecto, desde la fabricación hasta el montaje de componentes (Brugnaro et al, 2019). Muchos de estos errores se han resuelto en el estado del arte mediante la implementación de mecanismos de retroalimentación basados en sensores que permiten absorber las incongruencias entre la realidad física y los modelos digitales.…”
Section: Discussionunclassified
“…However, the automated assembly of discrete timber elements is still challenging, particularly in providing structurally reliable connections. Existing research has demonstrated robot assembly using glue-based [3,14,15] or nailed connections [7,16,17]. However, these solutions are not demountable and strongly limit the reusability of the timber elements and, thereby, the overall potential for material circularity.…”
Section: Introductionmentioning
confidence: 99%